2012
DOI: 10.3892/mmr.2012.1077
|View full text |Cite
|
Sign up to set email alerts
|

Side-effects of resveratrol in HepG2 cells: Reduced pten and increased bcl-xl mRNA expression

Abstract: Resveratrol is a natural compound present in red grapes and red wine, and is often consumed in the human diet. The chemopreventive and chemotherapeutic potential of resveratrol in hepatocellular carcinoma (HCC), one of the most common types of liver cancer, has received much attention in recent years. However, the side-effects of resveratrol stimulation are of concern due to the high doses administered to humans. This study investigated the effects of resveratrol on the mRNA expression of pten and bcl-xl in He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Resveratrol (3,4',5-trihydroxy-trans-stilbene), a natural polyphenol present in grapes, has been shown to inhibit intestinal tumorigenesis and modulate host-defense-related gene expression in an animal model of human familial adenomatous polyposis (Schneider et al, 2001), in addition to exerting anticancer effects on HepG2 cells (Zheng et al, 2012;Scherzberg et al, 2015), on human nasopharyngeal carcinoma (NPC) (Zhang et al, 2013), colon carcinoma (HT-29) and colorectal carcinoma (CaCo-2) (Scherzberg et al, 2015). Chen et al (2004) reported that resveratrol caused significant cytotoxicity and increased apoptosis and S-phase accumulation of neuroblastoma cells due to the down-regulation of p21 and up-regulation of cyclin E. Resveratrol analogs were efficient in inducing the accumulation of human colon cancer cells in early S-phase of the cell cycle.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Resveratrol (3,4',5-trihydroxy-trans-stilbene), a natural polyphenol present in grapes, has been shown to inhibit intestinal tumorigenesis and modulate host-defense-related gene expression in an animal model of human familial adenomatous polyposis (Schneider et al, 2001), in addition to exerting anticancer effects on HepG2 cells (Zheng et al, 2012;Scherzberg et al, 2015), on human nasopharyngeal carcinoma (NPC) (Zhang et al, 2013), colon carcinoma (HT-29) and colorectal carcinoma (CaCo-2) (Scherzberg et al, 2015). Chen et al (2004) reported that resveratrol caused significant cytotoxicity and increased apoptosis and S-phase accumulation of neuroblastoma cells due to the down-regulation of p21 and up-regulation of cyclin E. Resveratrol analogs were efficient in inducing the accumulation of human colon cancer cells in early S-phase of the cell cycle.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the identification of natural compounds with moderate cytotoxic activity is important, due to their easy availability, their low cost, and their ability to act effectively in reducing the incidence of cancer, without adverse side effects (Serra et al, 2013). In this sense, fox grapes (Vitis labrusca) and their derivatives stand out, because of their several nutritional, pharmacological and therapeutic benefits, such as in the treatment of cardiovascular diseases (Quiñones et al, 2013;Huang et al, 2015), liver and kidney disorders (Ulusoy et al, 2012;Charradi et al, 2013;Kim et al, 2013), and anti-tumor activity (Zheng et al, 2012;Zhang et al, 2013;Nivelle et al, 2017), especially due to the presence of phenolic compounds and their antioxidant activity (Fernandes et al, 2013;Maestre et al, 2013;Toaldo et al, 2015;Copetti et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Resveratrol is currently the topic of numerous animal and human studies, and although its anticancer effects have been reported, the underlying mechanism remains to be elucidated (2). During recent research, we found that resveratrol inhibits multiple myeloma cell proliferation and induces apoptosis through downregulation of STAT3 (3), which is a member of the STAT signaling protein family (4).…”
Section: Introductionmentioning
confidence: 98%
“…Resveratrol (3,4' ,5-trihydroxy-trans-stilbene; Rsv), a polyphenol mainly present in grapes and red wine, has numerous bioactivities, including the inhibition of tumor initiation, anti-inflammatory, lipid modification, anti-oxidative, neuroprotective and anti-aging effects (14)(15)(16). Resveratrol has received increasing attention and has been associated with its inhibition of the nuclear factor κ-light-chain-enhancer of activated B cells (NF-κB) transcription factor (17,18).…”
Section: Introductionmentioning
confidence: 99%